RR's Philippine almanac book of facts 1988- - Luna, Juan Luis, Jr. Z. (Aurora Publications, 1990)
The first 77 pages of this volume is a historical calendar. The following 28 chapters deal with all aspects of Philippine life and culture. Each chapter contains facts and statistics as well as trivia, helpful how-to-tips and guides, black and white illustrations, directories, and some humor. A general index is provided as well as seven pages of color maps and illustrations.